Epidemiological monitoring of leprosy indicators in Sergipe (2001-2015): segmented regression analysis, - Carlos Dornels Freire de Souza; Thiago Cavalcanti Leal; João Paulo Silva de Paiva; Victor Santana Santos (Sociedade Brasileira de Dermatologia, 2020)
Abstract This study analyzed the trend of leprosy indicators in Sergipe, between 2001 and 2015. It was a time series study that analyzed the trend for general detection coefficient, children under 15 years of age, and new cases with grade 2 disability. The joinpoint model was used. Two (2.6%) municipalities had an increasing trend in general detection coefficient, five (6.6%) had an increasing trend in detection rate in children under 15, and 19 (25.3%) had an increasing trend in detection coefficient of new leprosy cases with grade 2 disability. The findings suggest maintenance of the chain of transmission.